Upaya Transformasi Digital UMKM Desa Kalipecabean dengan Optimalisasi QRIS, Google Maps, dan E-Commerce - Manuel Vivien Ricardo Tampubolon; Masyura Fanni Ramadhan; Yafet Punta Rizky; Nifta Ardilia Putri; Nisrina Aulia Adzka; Dewi Puspa Arum (Universitas 45 Surabaya, 2024)
The digitalization program implemented for 13 MSMEs in Kalipecabean Village aimed to enhance transaction efficiency, business visibility, and digital skills of MSME entrepreneurs. This program involved the adoption of QRIS, registration on Google Maps, and integration with e-commerce platforms such as Shopee Food. The results showed significant improvements in transaction efficiency with QRIS, increased online visibility through Google Maps, and market expansion and sales growth through e-commerce platforms. The digital marketing training provided also enhanced the entrepreneurs' skills in utilizing social media and e-commerce for marketing. Despite some technical challenges still faced by a few entrepreneurs, this program demonstrated the effectiveness of a holistic and participatory approach in empowering MSMEs through digitalization, which can be replicated in other regions to support local and national economic growth.